Historia de las fiestas populares religiosas y su incidencia sociocultural en la vida de los habitantes de Riobamba desde el año 2000 hasta la actualidad. - Taipe León, Santiago Fabián (2016)
For decades, and year after year, religious celebrations in Riobamba have been of great importance, as these are part of the culture tradition of the citizens. The religious festivities of “Niño Rey de Reyes and the Semana Santa” or Easter are the most celebrated. The problema of this research is to identify if the public knows its true meaning, and history. So, the following questions arise: ¿What is the perception of Riobambeños on religious festivals like Niño Rey de Reyes and Semana Santa?. The Niño Rey de Reyes in Santa Rosa neighborhood wich is the most celebrated begins with the nine days of prayer and hosts for every day. After vespers, it ends the mass party which has a processions of the religious image through the main city streets with dances and music. Holy Week is a Catholic celebrations which recalls the life, death and resurrection of Jesus Christ. It begins with Palm Sunday and ends Easter Sunday, and according to research this act of faith was born in Seville, Spain, and arrives in Latin America with Religious Congregatiion, The nine days of prayer are carried out in many institutions and family homes and culminates with the Palm Sunday Mass. Holy Tuesday features a processions through the main streets of the city with the image of “Señor del Buen Suceso” or The Lord of Good Fortune who is the patrón saint of the city. Religious festivals are celebrated by tradition, without taking into account the origin and historical importance